Cult killer [videorecording (DVD)] - Burnley, Charles; Eve, Alice, 1982-; Hennig, Shelley, 1987-; Reid, Paul (Actor); Banderas, Antonio (Sony Pictures Home Entertainment, 2024)
A PI and his partner are drawn into a web of intrigue when they start tracking a serial killer targeting a wealthy family with a dark secret.